The Signaling Pathways Involved in Ovarian Follicle Development - Li, Liyuan; Shi, Xiaojin; Shi, Yun; Wang, Zhao (Frontiers in Physiology, 2021)
The follicle is the functional unit of the ovary, which is composed of three types of cells: oocytes, granulosa cells and theca cells. Ovarian follicle development and the subsequent ovulation process are coordinated by highly complex interplay between endocrine, paracrine, and autocrine signals, which coordinate steroidogenesis and gametogenesis. Follicle development is regulated mainly by three organs, the hypothalamus, anterior pituitary and gonad, which make up the hypothalamic-pituitary-gonadal axis. Steroid hormones and their receptors play pivotal roles in follicle development and participate in a series of classical signaling pathways. In this review, we summarize and compare the role of classical signaling pathways, such as the WNT, insulin, Notch and Hedgehog pathways, in ovarian follicle development and the underlying regulatory mechanism. We have also found that these four signaling pathways all interact with FOXO3, a transcription factor that is widely known to be under control of the PI3K/AKT signaling pathway and has been implicated as a major signaling pathway in the regulation of dormancy and initial follicular activation in the ovary. Although some of these interactions with FOXO3 have not been verified in ovarian follicle cells, there is a high possibility that FOXO3 plays a core role in follicular development and is regulated by classical signaling pathways. In this review, we present these signaling pathways from a comprehensive perspective to obtain a better understanding of the follicular development process.